Toilet Training Pada Anak Usia Dini 4-6 Tahun (Upaya Pembentukan Kemandirian di RA Nurul Islam) - Saftian Chayadi Hasibuan; Dina Armayani; Orin Fauzi Simatupang; Jumita Sari (AUD Cendekia, 2021)
This study aims to analyze the strategies, barriers, and collaboration between teachers and parents in teaching toilet training to children at RA Nurul Islam. This study uses a qualitative method, with a descriptive study approach. Data collection techniques using observation, interviews, and documentation studies. The results showed that the Toilet Training Strategy for Early Childhood 4-6 Years at RA Nurul Islam. Basic preparation, making the child interested, getting used to the toilet, don't scold him, giving praise. Barriers to Toilet Training Learning at RA Nurul Islam. There are several obstacles in teaching toilet training to students, some of which come from the students themselves and some of them come from outside the students themselves. Cooperation between teachers and parents in teaching toilet training to children Repetition of learning that has been taught at school at home. Exemplary cooperation Provision of facilities and facilities.